(untitled) (Mazahib, 2026)
This paper examines both the concept and application of taghrÄ«q (state confiscation of illegitimately acquired wealth) in Ibadi Islamic jurisprudence, addressing a gap in scholarship on Islamic public financial law. It situates the concept within Islam’s prohibition of unlawful enrichment and explores how justice may be restored when restitution to rightful owners is impossible. The study reveals that taghrÄ«q is a distinct Ibadi legal mechanism for addressing structural economic injustice, especially under illegitimate or oppressive rule. Methodologically, it combines doctrinal analysis of Ibadi legal texts with historical case studies from Oman, clarifying key concepts such as ghaá¹£b, Bayt al-mÄl, and jabbÄr, and examining precedents from early Islamic governance. It also outlines the legal conditions and scholarly debates governing taghrÄ«q. The findings indicate that taghrÄ«q is a regulated judicial tool applied when injustice is proven, ownership cannot be determined, and scholarly authorization is obtained. Historically, it enabled redistribution of illicit wealth for public welfare, forming a sophisticated Ibadi framework for financial accountability.